THE INFLUENCE OF DESTINATION IMAGE, EXPERIENTIAL QUALITY AND E-WORD OF MOUTH TOWARDS TOURIST REVISIT INTENTION TO TOMOHON CITY AS TOURISM DESTINATION - Michelle Maria Khrisanthi Kaunang; Maria Veronika J Tielung (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The aims of this study is to figure out the influence of destination image, experiential quality and e-word of mouth towards tourist revisit intention to Tomohon city. This research uses quantitative methods. To achieve this goal, the researchers distributed questionnaires and the sample used was 100 tourists as the respondents. The findings of this study indicate that Destination image, experiential quality and E-Word of Mouth simultaneously influence the revisit intention. Destination image and E-Word of Mouth have effect on tourists' revisit intentions. Meanwhile, Experiential Quality has no effect on revisit intention